Critique de la position du Conseil économique du Canada sur le libre-échange unilatéral - Shearer, Ronald (L'Actualité économique, 1976)
AbstractIn this article, the author proposes to focus on two related questions: Does the Economic Council's analysis suggest major theoretical errors in—or perhaps major theoretical challenges to—received doctrine on the nature of the impact of a unilateral removal of Canadian barriers to international trade? To what extent do the Economic Council's findings alter, extend or refine earlier quantitative assessments of the effects of unilateral free trade.The Council's analysis of the option of unilateral free trade is very brief. A very useful analysis of aspects of this option in the Dauphin study gets very little attention in the report itself. The conclusions on unilateral free trade are very much in the mainstream of Canadian thought on this matter, with perhaps some scaling down of the benefits imputed to unilateral tariff removal. The author finds two serious flaws in the otherwise useful discussion: a failure to give sufficient attention the implications of unilateral free trade for income redistribution within the country, and, in examining the implications of free trade for the long run structure of the economy, a failure to consider explicitly and thoroughly the interaction between the tariff and population and labour force growth, as suggested by Dales.